Amanita from Lateritic Region of West Bengal - Pradhan, Prakash; Banerjee, Subhankar; Roy, Anirban; Acharya, Krishnendu (Indian Forester, 2012)
Four species of Amanita were collected from lateritic region of West Bengal during the field trips of 2008-2009. One of the collected species Amanita vaginata was previously reported from this region; however three fungal species including. A. vaginata, A. vaginata var. Alba and A. banningiana are reported as new which were considered edible by the local residents.